KANDUNGAN NITRAT DAN FOSFAT DI PANTAI JUNGWOK, KABUPATEN GUNUNGKIDUL, YOGYAKARTA - Heny Budi Setyorini; Ernastin Maria (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2019)
Evaluation of nitrate and phosphate content in seawater of Jungwok Beach, Gunungkidul District, Yogyakarta, was the aim of this study. The method used was a survey with a quantitative approach. Sampling in the eastern, central and western regions of Jungwok Beach was carried out using a purposive sampling technique using line transects. At each site, there were three sampling points with distances of 0 meters, 5 meters and 10 meters from the coastline. One liter of water sample (at each point) was stored in polyethylene bottles. Nitrate and phosphate content analysis was conducted at the Laboratory of the Center for Environmental Health and Disease Control Engineering (BBTKLPP : Laboratorium Balai Besar Teknik Kesehatan Lingkungan dan Pengendalian Penyakit) Yogyakarta. Measurement of temperature, DO, pH and salinity were done in situ using the AZ8603 water quality monitor meter. The results showed that the nitrate concentration in Jungwok Beach ranged from 2.85 to 8.82 mg / l, while the phosphate ranged from 0.00 to 0.50 mg / l. Based on these results, the waters of Jungwok Beach are classified as mesotrophic to eutrophic waters. Overall the results of nitrate and phosphate have exceeded sea water quality standards for marine biota in the Decree of the Minister of Environment No. 51 of 2004 amounting to 0.008 mg / l and 0.015 mg / l. In situ measurement results showed that temperature, pH, DO and salinity at Jungwok Beach were respectively around 30.67 ± 0.93-32.20 + 0.62oC; 9.14 ± 0.29-9.29 ± 0.13; 8.00 ± 1.41-8.93 ± 1.19 mg / l and 34.83 ± 0.46-35.10 ± 0.10 ppt.